Perception of social participation in borderline personality disorder - Renneberg, Babette; Stäbler, Katja (Clinical psychology & psychotherapy, 2012)
Interpersonal dysfunction is a key feature of borderline personality disorder (BPD). Distorted perception of participation in social situations and altered emotional responses could contribute to these typical interpersonal problems in BPD. Thirty patients with BPD were compared with a healthy control group (n = 30) in their perceptions and subjective emotional reactions to situations of social inclusion and exclusion. Participants played Cyberball, a virtual ball-tossing paradigm, in which social inclusion and exclusion are experimentally induced. Control participants reacted with an increase in sadness, anger and overall negative affect when excluded. In BPD patients, social exclusion also induced anger, while general participating in the game seemed to reduce levels of sadness. Compared with healthy controls, BPD patients felt more readily excluded independent of the condition of inclusion or exclusion. In conclusion, patients with BPD displayed a negative bias toward perceived participation in social situations. Copyright © 2011 John Wiley & Sons, Ltd. Key Practitioner Message Patients with BPD have a biased perception for exclusion. Virtual ball-tossing games can be used to induce anger in patients with BPD. Participating in a virtual ball-tossing game may reduce levels of sadness in BPD in the short term.